Research Progress on Social Inclusion of Special Groups - Wang, Jie (International Journal of Social Sciences and Public Administration, 2024)
This paper reviews the concept and characteristics of special groups and the current situation of social integration of special groups. The special groups selected in this paper mainly include the disabled, people with mental disorders, released prisoners, orphans and the elderly who move with them. The social integration of these five groups is summarized, and the existing problems and future research directions are analyzed. The purpose is to provide a reference for the study of social integration of special population in China.